Eiropas apcietinājuma lēmums - Guļāne, Lāsma (Latvijas Universitāte, 2010)
This bachelor’s work deals with issue of a framework decision on the European arrest warrant and the surrender procedures between Member States of the European Union. The European Arrest Warrant, valid throughout the European Union has replaced earlier extradition procedures between Member States, such as the 1957 European Convention on Extradition (Council of Europe), that were applicable between the Member States. Such a warrant may be issued by a national issuing judicial authority if the person whose return is sought is accused, or if he has been sentenced to a prison term. The European Arrest Warrant means faster and simpler surrender procedures and no more political involvement. It also means that Member States can no longer refuse to surrender to another Member State their own citizens who have committed a serious crime, or who are suspected of having committed such a crime in another EU country, on the ground that they are nationals. Simplifying and improving the surrendering procedure between EU Member States was made possible by a high level of mutual trust and cooperation between countries who share the same highly demanding conception of the rule of law. Despite some initial delays, the European Arrest Warrant is now operational in most of the cases planned and its impact is positive, in terms of depoliticisation, efficiency, and speed in the procedure for surrendering people who are sought, while fundamental rights are respected throughout.
European arrest warrant
Keywords: Juridiskā zinātne